Roles of Edc3 in the oxidative stress response and CaMCA1‐encoded metacaspase expression in Candida albicans. (19th September 2014) - Jung, Jong‐Hwan; Kim, Jinmi
<x xml:space="preserve">Abstract</x> The Edc3 protein is an enhancer of mRNA decapping, and acts as a scaffold protein for the mRNA granules that are known as processing bodies in yeast. In the pathogenic yeast Candida albicans, various stresses, such as glucose depletion, oxidative stress, and filamentation defects, induce the accumulation of processing bodies. Here, we report that the edc3/edc3 deletion strain showed increased resistance to various stresses, including hydrogen peroxide, acetic acid, and high temperature. Oxidative stress is known to induce the intracellular accumulation of reactive oxygen species (ROS) and apoptotic cell death in C. albicans. We found that the ROS level was lower in edc3/edc3 cells than in wild‐type cells following oxidative stress. We also observed that expression of the metacaspase gene CaMCA1 was decreased in edc3/edc3 cells. Overexpression of CaMCA1 suppressed the decreased accumulation of ROS and the increased resistance to hydrogen peroxide in edc3/edc3 cells. The catalase Cat1 and the superoxide dismutase Sod1 were upregulated in edc3/edc3 cells as compared with wild‐type cells. On the basis of these findings, we suggest that EDC3 plays a critical role in the expression of CaMCA1 and the oxidative stress response in C. albicans.